In Vitro Analysis of Organic Ester Functional Groups in Carious Dentine - Mohammed Alturki; Ulrica Almhöjd; Garrit Koller; Fiona Warburton; Avijit Banerjee (Applied Sciences, 2022)
Background: With the implementation of minimally invasive selective caries removal protocols to treat cavitated, deep carious dentine lesions, there is a need to investigate specific biochemical moiety distributions to help characterise and distinguish between infected (contaminated) and affected (demineralised) zones within the dentine lesion. The present in vitro investigation aimed to compare the distribution of ester functional groups (1740 cm−1) within carious dentine tissue (infected and affected dentine). The null hypothesis stipulated that there are no differences in ester function intensity/distribution within carious dentine lesions. Materials and Methods: From a total of five extracted human molar teeth with carious dentine lesions, 246 points from 10 sections of carious dentine were examined using high-resolution Raman spectroscopy and characterised into infected, affected and sound dentine. The peak intensity of the characteristic vibration mode of the ester function was calculated from sample scans. Results: Analyses indicated a statistically significant difference in the spectroscopic vibration bands of esters between the infected and affected dentine zones. Conclusion: The ester functional group is higher in intensity in the caries-infected dentine zone compared to the affected tissue. This finding could be used to develop an objective indicator for the selective operative management of carious dentine.